Psychosocial Causes Affecting Inhalants Addiction in Children and Adolescents: Case Report - Ayşenur KARAASLAN (Hacettepe University, 2017)
The abuse of volatile substances as an exciting, stimulating and pleasure-oriented factor is widespread except in the industrial sector. In recent years, inhalants addiction has rapidly spread among children and adolescents. Indeed children andadolescents' use of substance may vary. Inhalants dependence is generally seen at average 14-15 years of age in the patients. When psychological reasons affecting volatile substance dependence are examined, it can be said that factors such as not knowing how to cope with stress in general, desire to get rid of negative and bad emotions, pleasure from matter, pleasure, wanting to belong to a group and feeling strong. When social factors are taken into consideration, it is first and foremost that access to volatile substances is easy and cheap, acceptance within the family, peer influence, positive perspective on the substance in the social environment and encouraging visuals in the social media.Here we present a case of psychosocial factors that cause alcohol and cannabis addiction in his family narrative, which begins to use volatile substance (lightergas) at the age of 12, in addition to inhalants, alcohol and cannabis